Healthy and unhealthy lifestyles as factors of occupational burnout in obstetrics and gynecology physicians - Mikhail Yu. Kuzmin; Darya P. Tyumentseva; Anait Yu. Marianian (Russian Open Medical Journal)
This article investigates healthy and unhealthy lifestyles and its components (physical activity, drinking alcohol, consumption of caffeinated products, tobacco use) as factors of occupational burnout in obstetrics and gynecology physicians. Material and Methods. A total of 132 physicians and nurses from the different clinics of Irkutsk were surveyed. We used Maslach Burnout Inventory (MBI), SF-12, and Godin Leisure-Time Exercise Questionnaire. Results: Differences in healthy and unhealthy lifestyles between physicians and nurses employed in obstetrics and gynecology, with or without a high burnout, were revealed. According to the obtained results, the frequency of alcohol consumption was directly related to burnout. In study subjects engaged in low and moderate physical activity, burnout occurred briefly or rarely. The differences became more pronounced when we excluded physicians and nurses with poor physical health from consideration, because they did not exercise much. According to the results of logistic regression, the probability of burnout and reduced level of quality of life among physicians and nurses increased with a bigger family size, lower work experience, and less time spent on moderate physical activity. Conclusion: Healthy and unhealthy lifestyles can cause healthcare employee burnout. Physicians and nurses with a high burnout consumed stronger alcohol and spent less time in moderate physical activity.